Personalized Image-Guided Therapies for Local Malignencies: Interdisciplinary Options for Interventional Radiology and Interventional Radiotherapy - Kovács, Attila; Bischoff, Peter; Haddad, Hathal; Kovács, György; Schaefer, Andreas; Zhou, Willi; Pinkawa, Michael (Frontiers in Oncology, 2021)
Minimal-invasive interventions considerably extend the therapeutic spectrum in oncology and open new dimensions in terms of survival, tolerability and patient-friendliness. Through the influence of image-guided interventions, many interdisciplinary therapy concepts have significantly evolved, and this process is by far not yet over. The rapid progression of minimal-invasive technologies offers hope for new therapeutic concepts in the short, medium and long term. Image-guided hybrid-technologies complement and even replace in selected cases classic surgery. In this newly begun era of immune-oncology, interdisciplinary collaboration and the focus on individualized and patient-friendly therapies are crucial.